DIGITAL TRANSFORMATION OF ACADEMIC LIBRARIES IN INDIA: EXPLORING ICT INTEGRATION FOR KNOWLEDGE SHARING AND RESOURCE OPTIMIZATION - Rajput, Awanish; Pandey, Praveen Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The digital transformation of academic libraries has revolutionized knowledge management practices, enabling enhanced knowledge sharing and resource management. This study investigates the role of Information and Communication Technology (ICT) in transforming academic libraries across Indian universities, with a specific focus on its impact on service delivery, knowledge dissemination, and resource optimization. The research explores various ICT applications such as digital repositories, integrated library systems, and collaborative platforms, highlighting their contributions to improving accessibility, efficiency, and user engagement. Despite the evident benefits, the study identifies challenges such as financial constraints, technological barriers, and the need for continuous skill development among library staff. Employing a mixed-methods approach, data was collected from selected university libraries in Jabalpur, Madhya Pradesh, using questionnaires and interviews. The findings reveal a significant adoption of ICT tools, with over 63% of participants acknowledging high standards of ICT-based knowledge management practices. This research underscores the importance of sustained investment in ICT infrastructure, enhanced training programs, and strategic policy development to overcome challenges and maximize the potential of ICT in academic libraries. By tending to these dimensions, libraries can cultivate an innovative and collaborative knowledge ecosystem that can help advance the academic achievement and research productivity of their institutions.